Memory, Forgiveness and Unfinished Justice in the Former Yugoslavia. Issue 4 (4th July 2017) - Akrivoulis, Dimitrios E.
Abstract: Drawing its examples from the case of the former Yugoslavia, the paper explores the difficult intersections of justice, memory and forgiveness where the present bears the traces of a violent past of inter-communal conflict and mass crimes. It specifically delves into the limits of institutional attempts to respond in a redemptory and permanent manner to the claims for justice in a political community scarred by such a tormenting past. It examines three judicial or semi-judicial manifestations of memory based on how they relate to the past(s) of the former Yugoslavia: (a) the punishment of the perpetrators, (b) the recognition of the crimes committed, and (c) forgetfulness in the name of peace and progress. Promoting reconciliation, governments often qualify a plea for forgiving as the last recourse to the impasse of institutional justice. At this fragile moment, forgiveness presents itself as a remedy for the impossibilities of institutional justice, without however fully evading the dangers of political expedience or the Western metaphysics of a 'universal' (Christian) ethos. Discussing memory as a dimension of justice, the paper concludes that if this intricate bond remains unexamined, the possibility of forgiveness in the former Yugoslavia could hardly attain any political meaning or vigour.